Inspeksi Pangan Sekolah Guna Pencegahan Penyakit Bersumber Pangan di Puskesmas Kota Ternate - Alfian S Ali; Novrianti Togubu; Tutik Lestari; Tati Sumiati; Ana Y Harum (UNIB Press, 2023)
The need for supervision and demands from the community regarding food safety guarantees, especially snacks for school children, are increasing. Supervision of food processing places is necessary to meet these needs and demands. Community service is carried out in the context of environmental health inspections at school food management sites. Method : The implementation through 3 stages: preparation, implementation and evaluation. Result : Not all TPPs in school canteens meet health requirements, there are still expired snacks, trash bins are not separated, the condition of the canteen is dirty and smells bad and the food served is not covered. Next, the team provided education to the canteen owner, confiscated expired food with the community health center, and reported it to the school. It is hoped that canteen owners and schools will make school canteens healthy.